NIPT for adult‐onset conditions: Australian NIPT users' views - Marks, IR; Devolder, K; Bowman‐Smart, H; Johnston, M; Mills, C (Wiley, 2024)
Noninvasive prenatal testing (NIPT) has become widely available in recent years. While initially used to screen for trisomies 21, 18, and 13, the test has expanded to include a range of other conditions and will likely expand further. This paper addresses the ethical issues that arise from one particularly controversial potential use of NIPT: screening for adult‐onset conditions (AOCs). We report data from our quantitative survey of Australian NIPT users' views on the ethical issues raised by NIPT for AOCs. The survey ascertained support for NIPT for several traits and conditions including AOCs. Participants were then asked about their level of concern around implications of screening for AOCs for the future child and parent(s). Descriptive and comparative data analyses were conducted. In total, 109 respondents were included in data analysis. The majority of respondents expressed support for NIPT screening for preventable (70.9%) and nonpreventable AOCs (80.8%). Most respondents indicated concern around potential harmful impacts associated with NIPT for AOCs, including the psychological impact on the future child and on the parent(s). Despite this, the majority of participants thought that continuation of a pregnancy known to be predisposed to an AOC is ethically acceptable. The implications of these data are critically discussed and used to inform the normative claim that prospective parents should be given access to NIPT for AOCs. The study contributes to a body of research debating the ethical acceptability and regulation of various applications of NIPT as screening panels expand.